Pelatihan Teknik Budidaya Lele Organik Dengan Metode BRL di Desa Lopak Aur - Hutwan Syarifuddin; Dodi Devitriano (Universitas Lancang Kuning, 2021)
The service has been carried out in the Yatim Mandiri Farmer Group, which consists of orphans in Lopak Aur Village, Pemayung District, Batanghari Regency. The implementation of the community service for 4 months from May to September 2020. The objective is to increase the knowledge and skills of farmer group members for catfish cultivation using the Eco-friendly Biofloc (BRL) method. The results of the dedication show that the orphan group has a high interest in cultivating catfish using the BRL technique. This is because catfish farming can be done without disturbing the school schedule of group members and the implementation is easy to do and provides economic value to meet the needs of orphans. The initial stage of catfish farming using the BRL technique has increased the knowledge and insight of orphans in trying to be independent. The prospect of catfish farming using the BRL technique can build an entrepreneurial spirit for orphans so that they can support the family economy.